COMMON PEONY – AS A PROMISING SOURCE OF RAW MATERIALS FOR THE CREATION OF MEDICINES - Sakhatska Іnna; Zakharchuk , Oleksandr; Horoshko , Oleksandra; Ezhned , Mariia (Collection of scientific papers «ΛΌГOΣ», 2024)
At present, herbal medicines occupy a significant part of both the national market and the leading markets of the world. According to experts, about 25% of medicines used in medical practice around the world are obtained directly from medicinal plant material. One of the most promising medicinal plants that can serve as a raw material for the production of new drugs is the common peony (Paeonia officinalis L.). The article presents the results of the analysis of literary and electronic sources of information on the distribution, chemical composition, pharmacological properties of medicinal peony, as well as the use of medicinal raw materials in medicine.